2016
DOI: 10.1128/aem.01672-16
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of Legionella pneumophila Serogroup 2 to 14 Isolates from Water Samples by Amplified Fragment Length Polymorphism and Sequence-Based Typing and Detection of Virulence Traits

Abstract: The aim of this study is to explore the dispersion, clonality, and virulence of Legionella pneumophila serogroups 2 to 14 in the Greek environment. Eighty L. pneumophila serogroup 2 to 14 strains isolated from water distribution systems of hotels, hospitals, athletic venues, and ferries in Greece were tested by monoclonal antibodies (MAbs) for serogroup discrimination and molecularly by amplified fragment length polymorphism (AFLP) for genetic diversity. Fifty-six of 80 strains were also typed by the sequence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 40 publications
5
25
3
1
Order By: Relevance
“…2 ) and also present in hospital water systems in Poland ( 31 ). In contrast, a 2-year surveillance study of a larger territory in Greece identified 10 different STs among 28 SG6 L. pneumophila strains isolated ( 51 ). More detailed genetic and phenotypic analyses of SG6 ST367 and ST461 strains from Flint, Detroit, Ontario, and Spain ( 33 , 35 ) can evaluate whether this L. pneumophila lineage is either endemic to Southeast Michigan, more readily recovered from water samples, or more fit in the physiochemical conditions peculiar to the 2014–2015 Flint municipal water system.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2 ) and also present in hospital water systems in Poland ( 31 ). In contrast, a 2-year surveillance study of a larger territory in Greece identified 10 different STs among 28 SG6 L. pneumophila strains isolated ( 51 ). More detailed genetic and phenotypic analyses of SG6 ST367 and ST461 strains from Flint, Detroit, Ontario, and Spain ( 33 , 35 ) can evaluate whether this L. pneumophila lineage is either endemic to Southeast Michigan, more readily recovered from water samples, or more fit in the physiochemical conditions peculiar to the 2014–2015 Flint municipal water system.…”
Section: Discussionmentioning
confidence: 97%
“…In the water distribution systems of nine hospitals in Poland, SG6 strains comprised 33% of the 11 environmental isolates, whereas SG1 strains accounted for 24% ( 31 ). In the Attica region of Greece, SG6 strains represented 62% of 37 L. pneumophila environmental isolates ( 51 ). In contrast, SG6 strains comprised only 15% of the L. pneumophila strains collected in England and Wales ( 46 ) and 11% of those isolated in France ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standardised SBT scheme for Lp presents an important advancement in the study of the molecular epidemiology of LD. It has been shown that the results obtained by different typing scheme for Legionella , such as PFGE and AFLP, are not necessarily concordant between them and also with SBT [ 13 , 14 ]. Implementation of SBT method has yielded comparable data worldwide and has been shown to be applicable in investigation of legionellosis outbreaks [ 1 ].The genetic variability of Lp has been assessed by SBT for countries such as the United-States, Canada, United-Kingdom, Germany, Spain, Belgium, Portugal, Italy, South Korea, China and Japan [ 3 , 19 21 , 43 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed-field gel electrophoresis (PFGE) and amplified fragment length polymorphism (AFLP) are two methods based on digestion of genomic DNA with restriction enzyme [ 9 ]. These two methods have been used both in outbreak investigation and for assessing genetic diversity of sporadic cases [ 10 14 ]. However, even though information provided is useful, their efficiency varies and most of them are not standardized [ 15 ].…”
Section: Introductionmentioning
confidence: 99%